Graphic Medicine: Comics Turn a Critical Eye on Health Care - Glazer, Sarah (The Hastings Center report, 2015)
A patient arrives in the emergency room apparently in a comatose state. But is he really unconscious or just faking? The young doctors on duty are skeptical. Failing to get a reaction with a chest rub, they try a variety of methods that become increasingly sadistic—pressing on the patient's fingernail with a ballpoint pen, spraying his testicles with a skin-freezing compound, announcing an imminent eye injection to scare the patient awake. I first encountered those chilling pen-and-ink images in a 2012 comic book, Disrepute, authored by Thom Ferrier, the nom de plume for British general practitioner Ian Williams. Disrepute is part of a young but growing genre that Williams helped dub 'graphic medicine' when he founded a website by that name in 2007. Using the graphic novel form, doctors, nurses, and patients are producing accounts that often reveal the dark underbelly of the world of medicine. From patients and their families, these include portraits of imperious and insensitive physicians or nurses; from doctors, explorations of the doubt that racks them when their treatment ends in a mistake or a patient's death. While the form is also referred to as “comics,” the work, as in Williams's strip, is bleak just as often as it is humorous.